DE CONTADOR A PROFESSOR DE CIÊNCIAS CONTÁBEIS: UMA INVESTIGAÇÃO (AUTO)BIOGRÁFICA A PARTIR DAS PROBLEMÁTICAS DA PRÁTICA PEDAGÓGICA E DA PESQUISA - Benadiba, Moses (2008)
Due to the proliferation of the Accounting Sciences High Education Courses, the Accounting Federal Council CFC has created the Sufficiency Examination because the teaching poor quality, giving, at such examination, emphasis to the ethical questions. Nowadays, the professional accountant has a practicalmechanical accounting knowledge larger than an accounting reasoning. This investigation, through my (auto)biographical trajectory study in a professional formation perspective, aims to identify the most determining elements in the Accounting Sciences Professor formation, and verify how much the investigation exercise has been present in this formation as well as examine if investigation, as an educational principle reflects itself in the teaching practice. It is necessary to understand that in the trajectory from Accountant to Accounting Sciences Professor, often results from an invitation to successful professionals in the area, who do not necessarily have the adequate pedagogical formation to teach. It is also the scope of this study, based on a better understanding of the practical aspects of a trajectory from an Accountant to Accounting Sciences Professor, to suggest some possible ways for the continuing education programs for these professors. Thus from the Education and Educators point of view, I assume as references Freire, Demo and Schön; from the High Education viewpoint, Cunha and Buarque; from the Accounting Sciences viewpoint, Iudícibus and Marion. The methodology utilized to elaborate this study was the (auto)biographical investigation, with reference, mainly, in Nóvoa and Josso. The results suggest that the tendency to reproduce the banking education, received at school from Elementary School to College, can only be reverted if the subject, without leaving the teaching practice job, has the opportunity to study the theoretical basis of the formal educative processes and to bring them to reflection upon his practice. The study demonstrates that the (auto)biographical investigation with the formative finality can be of great help in this reflexive process. Thus it is suggested that these strategies be utilized in the continuing education process of the Account Sciences Professors.(AU)